Stable glenoid component of reverse total shoulder arthroplasty at 2 years as measured with model-based radiostereometric analysis (RSA) - Alexander Nilsskog Fraser (Taylor & Francis Group, 2021)
Background and purpose — Reverse total shoulder arthroplasty (TSA) is used for treating cuff arthropathy, displaced proximal humeral fractures (PHF), and in revision shoulder surgery, despite sparse evidence on long-term results. We assessed stability of the glenoid component in reverse TSA, using model-based RSA. Patients and methods — 20 patients (mean age 76 years, 17 female), operated on with reverse TSA at Oslo University Hospital, in 2015–2017 were included. Indications for surgeries were PHFs, malunion, cuff arthropathy, and chronic shoulder dislocation. RSA markers were placed in the scapular neck, the coracoid, and the acromion. RSA radiographs were conducted postoperatively, at 3 months, 1 year, and 2 years. RSA analysis was performed using RSAcore with Reversed Engineering (RE) modality, with clinical precision < 0.25 mm for all translations (x, y, z) and < 0.7° for rotations (x, z). Scapular “notching” was assessed in conventional radiographs. Results — 1 patient was excluded due to revision surgery. More than half of the patients displayed measurable migration at 2 years: 6 patients with linear translations below 1 mm and 8 patients who showed rotational migration. Except for one outlier, the measured rotations were below 2°. The migration pattern suggested implant stability at 2 years. 10 patients showed radiolographic signs of “notching”, and the mean Oxford Shoulder Score (OSS) at 2 years was 29 points (15–36 points). Interpretation — Stability analysis of the glenoid component of reversed total shoulder arthroplasty using reversed engineering (RE) model-based RSA indicated component stability at 2 years.